Aflatoxin B1 in Rice Marketed in Lebanon - Kordahi, Rita (2021)
Rice is one of the world’s most staple food products. Being cultivated in subtropical and tropical hot and humid areas, A. flavus, A. parasiticus, and A. nomius fungi can contaminate rice and produce mycotoxins including the highly hepatotoxic and carcinogenic aflatoxin B1 (AFB1). Our study aimed to evaluate the AFB1 levels in packed rice marketed in Lebanon and determine the exposure to this toxin from the rice consumption. A total of 105 packed white, parboiled and brown rice bags were collected, among which 86 were from 43 brands collected during fall and spring. The enzyme-linked immunosorbent assay (ELISA) method was used to measure AFB1. A comprehensive food frequency questionnaire was filled by 200 participants to determine the patterns of rice consumption and subsequently the exposure levels to AFB1 from the rice consumption in Lebanon. AFB1 was detected in 105 out of 105 (100%) of the rice samples. The average concentration ± standard deviation of AFB1 was 0.5 ± 0.3 μg/kg. Contamination ranged between 0.06 and 2.08 μg/kg. Moisture content in all rice samples was below the limit (14%). Only 1% of the samples had an AFB1 level above the EU limit (2 μg/kg). Brown rice had a significantly higher AFB1 level than white and parboiled rice (p= 0.02), while a significant difference was found between both collections for the same brands (p= 0.016). Packing season, packing country, country of origin, presence of a food safety management certification, grain size, and time between packing and purchasing had no significant effect on AFB1 in rice. Exposure to AFB1 from rice consumption in Lebanon was calculated as 0.1-2 ng/kg bodyweight/day, resulting in 0.05-1.7 additional cancer cases/1,000,000 persons/year. Future studies should assess AFB1 in unpacked rice and routine monitoring must be carried out to take into account smuggled and emerging brands in the Lebanese market.